2023
DOI: 10.5847/wjem.j.1920-8642.2023.070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a low-cost instruction card for automated external defibrillator operation in lay rescuers: a randomized simulation study

Abstract: BACKGROUND: To evaluate whether a simplified self-instruction card can help potential rescue providers use automated external defibrillators (AEDs) more accurately and quickly. METHODS:From June 1, 2018, to November 30, 2019, a prospective longitudinal randomized controlled simulation study was conducted among 165 laypeople (18-65 years old) without prior AED training. A self-instruction card was designed to illuminate key AED operation procedures. Subjects were randomly divided into the card (n=83) and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…For the important outcome of adherence to a protocol or process assessed by a performance score, we identified very low certainty evidence (downgraded for very serious risk of bias, serious inconsistency and very serious impression) from five RCTs. 42 , 43 , 44 , 45 , 46 Three studies 42 , 43 , 44 investigating the use of mobile phone applications, demonstrated improved adherence to a process measured using a checklist or performance score. One study 45 investigating a mobile phone application using yes/no questions found no significant improvement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the important outcome of adherence to a protocol or process assessed by a performance score, we identified very low certainty evidence (downgraded for very serious risk of bias, serious inconsistency and very serious impression) from five RCTs. 42 , 43 , 44 , 45 , 46 Three studies 42 , 43 , 44 investigating the use of mobile phone applications, demonstrated improved adherence to a process measured using a checklist or performance score. One study 45 investigating a mobile phone application using yes/no questions found no significant improvement.…”
Section: Resultsmentioning
confidence: 99%
“…One study investigating the use of an instruction card by individuals found improved adherence to the sequence of AED use and improved time to shock. 46 …”
Section: Resultsmentioning
confidence: 99%